If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 12 = 2x + -7 + 12 Reorder the terms: 12 + 5x = 2x + -7 + 12 Reorder the terms: 12 + 5x = -7 + 12 + 2x Combine like terms: -7 + 12 = 5 12 + 5x = 5 + 2x Solving 12 + 5x = 5 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 12 + 5x + -2x = 5 + 2x + -2x Combine like terms: 5x + -2x = 3x 12 + 3x = 5 + 2x + -2x Combine like terms: 2x + -2x = 0 12 + 3x = 5 + 0 12 + 3x = 5 Add '-12' to each side of the equation. 12 + -12 + 3x = 5 + -12 Combine like terms: 12 + -12 = 0 0 + 3x = 5 + -12 3x = 5 + -12 Combine like terms: 5 + -12 = -7 3x = -7 Divide each side by '3'. x = -2.333333333 Simplifying x = -2.333333333
| 2x-4+2=10 | | 6x-59=-71 | | 4(x+7)+5x=9x-28 | | x^4+11x-30=0 | | -5x+16=-39 | | 12m=-52+112 | | 2i-y= | | -18+z=5 | | -28+7x=28 | | =11p | | -m^2+11m=0 | | =10p | | -75=-5(-5+n) | | 4x^2-17x+7=-9+4 | | =5p | | 8x+3y=42-20x | | 4x^2-28x+98=0 | | x^2-4x-3=-2x+5 | | 6(5+5n)= | | x^2-3x-23=5 | | 4r^2-36=0 | | X-26=-41 | | 11=(-4x-4)+x | | (x-3)(x-1)-48=0 | | 4(x+2)-4x-2=4 | | 6y^2+44y-90=0 | | (-1+45x)+(23x)=135 | | 7s-10=-3 | | 3-4r+2=2r-6(r-3) | | 80=-5(2x-4)-5x | | 2-7r+7=2r-9(r-1) | | -5x-2y=-14 |